Nanoscale tailor-made membranes for precise and rapid molecular sieve separation - Wang, J.; Zhu, J.; Zhang, Y.; Liu, Jian; Van Der Bruggen, B. (R S C Publications, 2017)
© 2017 The Royal Society of Chemistry. The precise and rapid separation of different molecules from aqueous, organic solutions and gas mixtures is critical to many technologies in the context of resource-saving and sustainable development. The strength of membrane-based technologies is well recognized and they are extensively applied as cost-effective, highly efficient separation techniques. Currently, empirical-based approaches, lacking an accurate nanoscale control, are used to prepare the most advanced membranes. In contrast, nanoscale control renders the membrane molecular specificity (sub-2 nm) necessary for efficient and rapid molecular separation. Therefore, as a growing trend in membrane technology, the field of nanoscale tailor-made membranes is highlighted in this review. An in-depth analysis of the latest advances in tailor-made membranes for precise and rapid molecule sieving is given, along with an outlook to future perspectives of such membranes. Special attention is paid to the established processing strategies, as well as the application of molecular dynamics (MD) simulation in nanoporous membrane design. This review will provide useful guidelines for future research in the development of nanoscale tailor-made membranes with a precise and rapid molecular sieve separation property.